Extracurricular Participation, School Size, and Achievement and Self-Esteem Among High School Students: A National Look - Theodore Coladarci (Journal of Research in Rural Education, 1996)
Using the NELS:88 database, we examined (a) the relation betweenschool size and extracurricular participation (EP) in high school, (b) the effect ofEP on 12th-grade academic achievement and self-esteem, and (c) the indirect effect ofschool size on achievement and self-esteem through its effect on EP. Consistent with the seminal study by Barker and Gump et al. (1964), we found higher EP among smaller-school students across various activities. We also uncovered a significant, if modest, effect ofEP on self-esteem, but no meaningful effect on achievement. The indirect effect ofschool size on either outcome, through its effect on EP, did not obtain. Thus, there is no basis in our data to support· the proposition that smallerschools, through their positive effects on extracurricular participation,foster either academic achievement or self-esteem